The Effect of a Combined Scapula and Shoulder Exercise Program with Kinesio Tape on Pain, Shoulder Proprioception, and Upper Limb Function in Swimmers with Shoulder Impingement Syndrome - Seyedeh Farzaneh Sadri; Mohammad Saleki (Biyumikānīk-i varzishī)
Objective The present study aimed to determine the effect of a combined scapula and shoulder exercise program with Kinesio Tape on pain, shoulder proprioception, and upper limb function in swimmers with shoulder impingement syndrome. Methods In this study, 30 swimmers with shoulder impingement syndrome were purposefully selected and randomly divided into two groups: a control group (15 participants) and an exercise group (15 participants). After completing the consent form, anthropometric measurements, including height and weight, were taken. Pain was assessed using the Visual Analog Scale (VAS), shoulder proprioception was measured using a goniometer, and upper limb function was evaluated using the Upper Limb Y Test. The exercise group performed the prescribed exercises for 8 weeks, with three sessions per week. After the training program concluded, post-tests were administered. To compare the research variables between the experimental and control groups, analysis of covariance (ANCOVA) and paired t-tests were used. If the data were not normally distributed, the Mann-Whitney U test and Wilcoxon signed-rank test were employed to compare the groups and assess the effect of the training. All statistical analyses were performed using SPSS version 24. Results The results showed that the exercise program had a significant effect on reducing pain (p=0.001), increasing proprioception (p=0.002), and improving upper limb function (p=0.001). Additionally, intergroup comparisons revealed a significant difference between the two groups in the variables of pain (p=0.004), proprioception (p=0.001), and upper limb function (p=0.001). Conclusion Overall, the results of this study demonstrate the effectiveness of a combined scapula and shoulder exercise program with Kinesio Tape in reducing pain, enhancing proprioception, and improving upper limb function in swimmers with shoulder impingement syndrome. These findings underscore the importance of incorporating these exercises to enhance the health and performance of swimmers affected by this condition.